35. THE RESULTS OF BLASTOCYST FORMATION RATE WHEN INJECTING HIGH DNA FRAGMENTATION INDEX SPERM INTRA-CYTOPLASMIC (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of blastocyst formation rate injecting sperm with high fragmentation index (DFI ≥ 30) incubated with follicular fluid and injected intra-cytoplasmic. Subjects and Methods: A cross-sectional descriptive study was conducted on 1,383 oocytes from 110 couples undergoing in vitro fertilization (IVF) at the Center for Assisted Reproduction and Andrology - Phu Tho Obstetrics & Pediatric Hospital. The fertilization results, embryo formation (Day 3) and blastocyst formation (Day 5 and 6) were compared between the study group (injected high DFI sperm incubated with follicular fluid) and the control group (injected high DFI sperm not incubated with follicular fluid).Results: The fertilization rate, Day 3 embryo rate, Day 3 embryo rate (grade 1 + grade 2), blastocyst rate and blastocyst rate (grade 1+ grade 2) of the study group compared to the control group showed statistically significant differences: 90.4% vs. 81.6%, p < 0.05; 100% vs. 99.2%, p < 0.05; 57.5% vs. 50.9%, p < 0.05;  65.7% vs. 47.7%, p < 0.05; and 63.5% vs. 32.4%, p < 0.05, respectively.Conclusion: The fertilization rate and the blastocyst formation rate in the study group higher the control group, particularly the blastocyst rate (grade 1+ grade 2) in the sudy group with double for the control group.
Keywords: High sperm DNA fragmentation index; ICSI; blastocyst